Effects of Counterfeits on Branded Products in Garments Industry: A Perspective on Consumer Behaviour - Gul, Arbab; Muhammad Ali; Muhammad Ahmad Khan Qazi; Nuzulul Fatimah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
Counterfeit products are fake replicas of the real products. Deceptive counterfeits buying (consumer is well-aware about counterfeits) and non-deceptive counterfeits buying (consumer is not aware of counterfeits) are two dimensions of counterfeits buying. In Pakistan counterfeiting is an embryonic issue for many markets i.e., cosmetics, cellular, electronics, home appliances, and medicines. Furthermore, in last decade counterfeiting predominantly affect the garment’s market of branded products in Pakistan. This study aims to investigate the counterfeit effects on consumer buying perception of branded garments products. The various determinants used in this research for counterfeit brands’ purchase intentions and attitude towards counterfeits in Pakistani context have not been used in the way as they are used in the current research. After the data analysis it has been found that Purchase Intention of branded products and Attitude towards the branded products have positive significant impact on Counterfeits Products. Perceived quality of branded products has negative significant impact on counterfeits products while Status consumption has no significant impact on counterfeits Products.